The US earned income tax credit, its effects, and possible reforms - Bruce D. Meyer (Institute for Labour Market Policy Evaluation (IFAU), 2008)
In this paper, I first summarize how the US Earned Income Tax Credit (EITC) operates and describe the characteristics of recipients. I then discuss empirical work on the effects of the EITC on poverty and income distribution, and its effects on labor supply. Next, I discuss a few policy concerns about the EITC: possible negative effects on hours of work and marriage, and problems of compliance with the tax system. I then briefly discuss some possible reforms to the structure of the current EITC.
Keywords: D31; H24; I38; J38; 330; Welfare reform; Earned income tax credit; EITC; Earnings subsidies; Tax credits; Poverty; Sozialpolitik; Niedrigeinkommen; Steuerpolitik; Familienbesteuerung; Steuerbegünstigung; Einkommensverteilung; Armut; USA